THEMATIC QUR’ANIC INTERPRETATION AND IMPLEMENTATION OF ENVIRONMENTAL CONSERVATION IN INDONESIA’S SUSTAINABLE DEVELOPMENT - Hamidatun Nihayah; Yuyun Affandi; Akhmad Arif Junaidi; Bendaoud Nadif (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2025)
The Qur’an emphasizes the importance of environmental conservation and appoints humankind as khalīfah (stewards) on earth. Although widely discussed, these values largely remain unoperationalized within applied ecological frameworks. Addressing this research gap, this study aims to explore and actualize Qur’anic values of environmental conservation through a thematic (mawd}ū’ī) exegesis approach. Using library research, the analysis identifies and interprets Qur’anic verses related to ecological ethics. The findings reveal three key dimensions of conservation values: protection, encompassing amānah (trust), human responsibility as khalīfah, and gratitude; preservation, which includes ecological justice, rah}mah (compassion), tawh}īd (divine oneness); and sustainable utilization, centered on the prohibition of isrāf (wastefulness) as a principle of balance. This study presents a novel synthesis between Qur’anic eco-ethics and Indonesia’s sustainable development discourse, a connection that has rarely been examined in previous thematic exegesis research. In the Indonesian context, the implementation of these values reflects initiatives such as eco-pesantren and eco-mosque movements, as well as environmentally conscious public policies aligned with local wisdom and the Sustainable Development Goals (SDGs) 2030. Thus, Qur’anic ecological ethics not only enrich Islamic scholarship but also contribute to building a just, sustainable, and spiritually grounded civilization.